Performance Test Of Pressurized Stove Using Kapok (Ceiba petandra) Oil As An Alternative Fuel - Susilo, Bambang; Argo, Bambang Dwi; Rakhmawati, Aulia (Jurnal Teknologi Pertanian, 2007)
The aim of the experiment is to analyze the influence of transesterification and degumming processes to the physical characteristic of kapok oil and to know the combustion performance of pressurized stove using oil result from degumming and transesterification. The performance test of pressurized stove consists of two factors. First factor is pressure (0.7 and 1 bar), the second factor is the kind of fuel; kerosene, degumming and transesterification. The result shows the combustion performance of pressurized stove using oil from transesterification process has the same performance using kerosene, this is evaluated from the physical characteristic of the oil and the combustion performanced. The physical characteristic analyzed were viscosity, density and calorific value, while the parameters of pressurized stove performance that was monitored were burning time, flame quality, nozzle clogging, fuel consumption, burning velocity, burn efficiency and stove energy. The pressure of pressurized stove was significant influence to the fuel consumption, flaming velocity, burn efficiency, and stove energy.Key words: Kapok oil, degumming, transesterification, pressurized stove